The Role of Artificial Intelligence in Infectious Diseases: A Review of Mathematical Modeling Approach and Awareness. - Adisa, I.O; Onanaye, A.S. (Corpus Intellectual, 2025)
This paper focuses on the role of Artificial Intelligence (AI) of infectious diseases. AI is the intelligence of machines or computers that enables them to imitate human capabilities. Infectious diseases are illnesses caused by harmful agents such as bacteria, viruses, fungi, and parasites. Mathematical modeling approach is considered since it is an important tool in scientific research which enables researcher to describe, test, predict and gain deeper understanding. Public enlightment or awareness of infectious diseases is crucial for prevention, early detection and effective treatment.